PENGARUH TRANSFORMASI TEKNOLOGI GLOBAL TERHADAP INOVASI STRATEGIK DALAM INDUSTRI PENDIDIKAN - Hartinah Idrus; Yuliana A; Sandy Aulia Putri (Al-Mumtaz: Jurnal Manajemen Pendidikan Islam, 2025)
The global technological transformation has had a significant impact on various sectors, including the education industry. Advances in digital technology, particularly in the fields of the internet and educational software, have changed the way education is delivered, managed, and accessed. Technology not only facilitates new methods of delivering learning materials but also drives strategic innovations in curriculum management and teaching methods. This study aims to analyze the impact of global technological transformation on strategic innovation in the education sector by using a literature review method to examine relevant previous studies, including journal articles, books, and government reports. The results of the study indicate that the adoption of technologies such as online learning, learning management systems (LMS), and data-driven applications has transformed the traditional paradigm of education and introduced more flexible, personalized, and integrated learning models. Nevertheless, the implementation of technology faces major challenges, such as limited infrastructure, resistance to change, the digital divide, and issues related to data privacy and security. Therefore, to maximize the potential of technology in education, policies that support equitable access, digital skills training, and infrastructure enhancement are needed to bridge the digital divide, enabling technology to drive more effective and sustainable innovation in the education industry.